Antioxidative and Antimelanoma Effects of Various Tea Extracts via a Green Extraction Method. (13th February 2018) - Chen, Yihui; Huang, Jyun-Yin; Lin, Yichi; Lin, I-Fan; Lu, Yi-Ru; Liu, Li-Heng; Wang, Hui-Min David
Abstract : Tea (Camellia sinensis) contains high level of antioxidant elements and is a well-known beverage consumed worldwide. The purpose of this study is to compare different concentrations of green tea, black tea, oolong tea 861, oolong tea 732, and jasmine green tea. These five types of tea extracts were known to have antioxidative properties, reducing power, and metal ion chelating activity. The current study compared these five extracts in terms of their inhibiting effects on human malignant melanoma: A2058 and A375. To determine the cell viability between normal cell and malignant melanoma cells, an MTT assay was applied to evaluate the cytotoxic potential on human melanoma cells, with all tea extracts showing decreased cell viability with increasing tea extract concentrations. Cytotoxicity on HaCat (normal skin cells) showed no effect on the cell viabilities at lower concentrations of the tea extracts. These results suggest the antioxidative effect of five tea extracts that protect against oxidation and melanoma production, with green tea and jasmine green tea showing the lowest cell viability when tested against malignant melanoma cells.